Trade agreements and their relation to labour atandards: The current situation - Pablo Lazo Grandi (International Centre for Trade and Sustainable Development (ICTSD), 2009)
The study provides a political and legal review of how international labour standards have been introduced and how those standards have evolved in the international trade arena. The author analyses new trends and negotiations on trade and labour standards at the multilateral, regional, and bilateral levels. The aim of the study is to offer developing country governments and other relevant stakeholders broad guidelines on how to address these issues in international negotiations with a focus on RTAs, taking into account the experience of countries such as Chile that have already negotiated several of those agreements. Many of these agreements contain some similar baseline clauses including objectives, scope, and minimum international standards. There is also a certain level of divergence in those agreements, especially in relation to specific commitments, arrangements for compliance and dispute resolution clauses. In some cases, countries have adopted co-operation provisions and programmes for improving their capacity for inspection and control ...
Keywords: 330